MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-CONCEPT CALON GURU DI KABUPATEN KARAWANG MELALUI PENDEKATAN OPEN-ENDED - Hendra Kartika (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
This study aims to investigate open-ended learning approach in improving undergraduate students’ mathematical problem-solving ability and self-concept toward linear algebra subject. Population in this study is mathematics education students FKIP Unsika in four semesters that takes linear algebra courses while the sample is two classes became experiment class and control class. The research design that used in this study is non-equivalent control group design. Results show that undergraduate students’ mathematical problem-solving ability and self-concept who followed open-ended learning approach were fostered significantly compared to undergraduate students’ who received conventional teaching method.